Production Factors of Processed Nets in Pingaran Village, Astambul District - Inayatul Khadijah; Bambang Subiyakto; Sigit Triyono; Syarifuddin Syarifuddin; Fatwa Nur’aini (The Innovation of Social Studies Journal, 2025)
Jaring is a traditional food typical of the Banjar tribe and Pingaran Village is one of the processed centers of Jaring. This traditional food is made with a hereditary recipe that highlights the authentic taste and distinctive way of serving using Tailala sauce. However, business actors face challenges in the form of limited raw materials due to dependence on external supplies and simple marketing strategies. The purpose of this study is to describe the Production Factors of processed Nets in Pingaran Village, Astambul District. The research method used is a qualitative descriptive method that aims to describe and explain the state of the object being studied by observation, interview, and documentation techniques. Data analysis is carried out by reducing data, presenting data, and making conclusions to ensure the validity of the data, this study applies triangulation. The results of this study are related to the Production Factors of processed Nets (1) Labor which is dominated by family roles (2) Capital sourced from the business owner's personal funds, which is Rp. 6,000,000 which is allocated to buy raw materials consisting of Nets, Coconut, and Firewood, (3) Raw materials, namely Nets or Jengkol which are supplied from outside the region,   and (4) Entrepreneurship is shown by the innovation of business owners in maintaining the traditional flavor of the hereditary business. The conclusion of the Jaring processed business in Pingaran Village is supported by four main production factors: the involvement of family labor, independent capital, limited raw materials that are still utilized, and entrepreneurial innovation. This business has an economic impact while preserving local culture, so that it has the potential to improve the welfare of the community in a sustainable manner.